Industry-Oriented Experiential Learning Model to Enhance Vocational High School Students' Job Readiness - Sudarsono, Bambang; Tentama, Fatwa; Ghozali, Fanani Arief; Listyaningrum, Prabandari (Journal of Education Reseach and Evaluation, 2023)
The highest unemployment rate in Indonesia is still dominated by SMK graduates. Unemployment occurs because the work readiness of SMK students is low. This study aims to develop an industrial-oriented experiential learning model and test its effectiveness. This study used a research and development (R&D) design from Richey and Klein. The research stages include the stages of needs analysis, internal validation and external validation. The research subjects used were teachers, students majoring in automotive engineering at SMK Muhammadiyah 1 Salam and automotive industry practitioners, totaling 44 people. Data collection techniques used were interviews, questionnaires and performance tests. Researchers analyzed descriptively to produce conclusions from the feasibility of questionnaires and learning models. After being analyzed, the results of the questionnaire and practical performance tests were categorized to produce conclusions for each instrument. The result of the study show that industrial-oriented experiential learning model is very suitable to be applied to vocational learning. Vocational schools can broadly collaborate with industry, teachers and students gain knowledge and skills according to the needs of the world of work and motivation arises to make industrial replicas of learning infrastructure.